Self-Control and the Effects of Movie Alcohol Portrayals on Immediate Alcohol Consumption in Male College Students - Koordeman, Renske; Anschutz, Doeschka J.; Engels, Rutger C. M. E. (Frontiers in Psychiatry, 2015)
Abstract Background: In movies alcohol-related cues are frequently depicted and there is evidence for a link between movie alcohol cues and immediate alcohol consumption. Less is known about factors influencing immediate effects movie alcohol exposure on drinking. The exertion of self-control is thought be important in avoiding or resisting certain temptations. Aims: The aim of the present study was to assess the immediate effects of movie alcohol portrayals on drinking of male social drinkers and to assess the moderating role of self-control in this relation. It was hypothesized that participants would drink more when exposed to movie alcohol portrayals and that especially participants with low self-control would be affected by these portrayals. Methods: A between-subjects design comparing two movie conditions (alcohol or no portrayal of alcohol) was used, in which 154 pairs of male friends (ages 18-30) watched a 1-hour movie in a semi-naturalistic living room setting. Their alcohol consumption while watching was examined. Participants completed a questionnaire assessing self-control as well as their self-reported weekly alcohol use. A multivariate regression analysis was conducted to test the effects of movie condition on alcohol comsumption. Results: Self-control moderated the relation between movie condition and alcohol consumption. Assignment to the alcohol movie condition increased alcohol consumption during the movie for males with high self-control but not for males with low self-control. Conclusion: Viewing a movie with alcohol portrayals can lead to higher alcohol consumption in a specific sample of young men while watching a movie.